Variation of Physical Properties of Eucalyptus globulus Grown in Ethiopia - Waktole, Samson; Musa, Mahadi; Abara, Lamesa; Mezegebu, Getachew; Wale, Meseganaw; Wubeshet, Tsegaye; Tesfaye, Anteneh (CV. Literasi Indonesia, 2024)
This study investigated the variability of density, shrinkage, and sap-heartwood proportion in different sites and within a tree. 10 trees of E. globulus from Menagesha Suba (M/Suba) and Debre Birhan (D/Birhan) forests were felled and 12 disks from each tree were collected along the stem. From each disk blocks of 2*2*3cm were taken at three locations from pith to bark. Then the block's green and oven dry weights as well as the three dimensions were measured. The result showed that the density and radial shrinkage of trees from M/Suba were significantly higher than D/Birhan forest. However, tangential, longitudinal shrinkage and sapwood proportion of trees from D/Birhan were significantly higher than M/Suba forest. Along the height, at both sites, density was increasing from bottom to top. In both sites, all shrinkages had shown a decreasing trend from breast height to 40%. Sap-heartwood proportions were irregular in trend along the height in both sites. Density shows an irregular pattern radially at both sites. At M/Suba, radial and tangential shrinkages increased from pith to bark. However longitudinal shrinkage exhibited a decreasing trend from pith to bark. At the D/Birhan forest, all shrinkages showed irregular patterns from pith to bark. Density was highly variable along the height in both study sites. Radially, density was more variable in the D/Birhan site. This study recommended that for end-uses requiring durable, denser, and stable wood, E. globulus from the M/Suba forest was better. For pulp wood, E. globulus from D/Birhan was recommended.